1995
DOI: 10.1057/palgrave.jibs.8490818
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of Strategy and Structure in Subsidiaries of Multinational Corporations

Abstract: A three-fold typology of subsidiary roles (world mandate, specialized contributor, local implementer) was induced from the literature and its empirical validity was confirmed. Adopting a configurational approach, we then explored the ways in which subsidiary 'structural context' varied across subsidiary role types. Structural context characteristics were determined through a discussion of the underlying principles of the 'hierarchy' and 'heterarchy' models of multinational organization. The key findings were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
495
4
27

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 682 publications
(535 citation statements)
references
References 42 publications
9
495
4
27
Order By: Relevance
“…Note, that including these variables did not change substantive findings, that is, they were in fact Bimpotent^in the present analysis (Becker, 2005). The first was a five-item measure of resource sharing taken from Davis, Desai, and Francis (2000) (α = .74) as research has suggested that high levels of resource sharing between the parent firm and the foreign subsidiary leads to higher extents of control (Andersson & Forsgren, 1996;Birkinshaw & Morrison, 1995). Second, we assessed the level of asset specificity using items developed by (α = .78).…”
Section: Control Variablesmentioning
confidence: 71%
See 1 more Smart Citation
“…Note, that including these variables did not change substantive findings, that is, they were in fact Bimpotent^in the present analysis (Becker, 2005). The first was a five-item measure of resource sharing taken from Davis, Desai, and Francis (2000) (α = .74) as research has suggested that high levels of resource sharing between the parent firm and the foreign subsidiary leads to higher extents of control (Andersson & Forsgren, 1996;Birkinshaw & Morrison, 1995). Second, we assessed the level of asset specificity using items developed by (α = .78).…”
Section: Control Variablesmentioning
confidence: 71%
“…We challenge this notion under certain conditions. For example, research on Bsubsidiary mandate^clearly indicates that even within the same type of ownership modes, parent firms may have varying levels of control over foreign subsidiaries, depending, for example, on their contribution of firm-specific assets (Birkinshaw et al, 1998) or the type of mandate they develop within the global MNC network (Birkinshaw & Morrison, 1995). These scholars identify determinants of operational control (or autonomy) in foreign subsidiaries and acknowledge that subsidiaries differ in terms of their extent of control; however, they do not take the type of ownership mode into account.…”
mentioning
confidence: 99%
“…Las empresas multinacionales no se pueden comprender como un entramado homogéneo dirigido completamente desde el centro (Birkinshaw, 2000). La planeación, la coordinación y el control se vuelven más difíciles, no solamente a causa de las distancias geográficas; la capacidad de la cúpula empresarial para controlar las relaciones entre la sede central y las sucursales en el extranjero se pone en entredicho gracias a la existencia de amplias zonas de incertidumbre, a las relaciones de poder y de conocimiento y a las rivalidades internas (Kristensen, et al, 2005).…”
Section: Alcances De La Aplicación De Los Autocompromisosunclassified
“…La planeación, la coordinación y el control se vuelven más difíciles, no solamente a causa de las distancias geográficas; la capacidad de la cúpula empresarial para controlar las relaciones entre la sede central y las sucursales en el extranjero se pone en entredicho gracias a la existencia de amplias zonas de incertidumbre, a las relaciones de poder y de conocimiento y a las rivalidades internas (Kristensen, et al, 2005). También las gerencias locales ganan y aspiran a márgenes de juego para su autonomía frente a las centrales, debido a que las sucursales están incorporadas a tradiciones culturales, sistemas de negocios y mercados diversos, de acuerdo con los contextos institucionales nacionales específicos, que plantean a su turno un diverso tipo de exigencias de acomodación (Birkinshaw, et al, 1995). En los países anfitriones sólo pueden elaborar sus productos y ofrecer sus servicios como organizaciones inmersas en lo local.…”
Section: Alcances De La Aplicación De Los Autocompromisosunclassified
See 1 more Smart Citation